2009
DOI: 10.1111/j.1365-2214.2008.00920.x
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety and stress in mothers and fathers in the 24 h after their child's surgery

Abstract: Background and objective Surgery in a paediatric setting stresses children and their parents. Previous studies have focused on children and the preoperative period; however, the 24 h after child surgery are highly stressful for parents as their child is still physically recovering and physician–parent communication is vital. The aims of this study are to investigate the impact of three levels of severity of paediatric surgery on mothers’ and fathers’ anxiety and stress and to identify factors that contribute t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
82
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 17 publications
(21 reference statements)
7
82
1
2
Order By: Relevance
“…7,8 Yine çocuklardaki çeşitli hastalıkların ebeveynlerin anksiyete düzeylerine etkisini inceleyen başka araştırmalar da vardır. [9][10][11][12][13][14] Ancak, bu araştırmaların çoğunluğu da belli bir hastalığı olan veya yoğun bakım, ameliyat gibi özel bir müdahale gerektiren çocukların ebeveynleri ile ilgilidir. …”
Section: Introductionunclassified
“…7,8 Yine çocuklardaki çeşitli hastalıkların ebeveynlerin anksiyete düzeylerine etkisini inceleyen başka araştırmalar da vardır. [9][10][11][12][13][14] Ancak, bu araştırmaların çoğunluğu da belli bir hastalığı olan veya yoğun bakım, ameliyat gibi özel bir müdahale gerektiren çocukların ebeveynleri ile ilgilidir. …”
Section: Introductionunclassified
“…Five of the six parents who participated were mothers and one was a father. The sample most probably reflects reality as Scrimin et al (2009) have reported that it is more often mothers, who are present at their child's anesthesia. The result in the present study can, however, be influenced as previous research has shown that mothers are generally more worried for their children in this specific situation (Chorney & Kain 2010;Messeri, Capprillo & Busoni 2004;Scrimin et al 2009).…”
Section: Discussion Of Methodologymentioning
confidence: 99%
“…Scrimin, Haynes, Altoè, Bornstein and Axia (2009) show that 47% of parents are worried and 26% have symptoms of stress. Parents' worry, when a child is to be anaesthetized, is at its highest level for the anaesthesia induction.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the impact of dramatic health events on family members. For example, a spell in the intensive care unit has been associated with post-traumatic stress reaction in a high proportion of family members [Jones et al, 2004;Paparrigopoulos et al, 2006] and with major life changes and increases in care-giving, as well as loss of the major source of family income [Covinsky et al, 1994;Swoboda and Lipsett, 2002] Other studies have found high levels of parental anxiety and stress following child surgery [Scrimin et al, 2009] and persistence of psychological distress following hospitalizations for child head trauma [Youngblut and Brooten, 2006].…”
mentioning
confidence: 98%